The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1101/2021.03.28.437410
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TOR represses stress responses through global regulation of H3K27 trimethylation in plants

Abstract: Combinations of epigenetic modifications H3K4me3 and H3K27me3 implicate bistable feature which alternates between on and off state allowing rapid transcriptional changes upon external stimuli. Target of Rapamycin (TOR) functions as a central sensory hub to link a wide range of external stimuli to gene expression. However, the mechanisms underlying stimulus-specific transcriptional reprogramming by TOR remains elusive. Our in silico analysis in Arabidopsis demonstrates that TOR-repressed genes are associated wi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…Most of the genes with the increased DNA methylation are involved in nutrients metabolism (carbon and AAs) and phytohormones signaling transduction processes, which are tightly connected with plant growth and development (Zhu et al, 2020). Moreover, TOR could repress the transcription of stress-related genes by global maintenance of the histone modification at H3K27me3 (Dong et al, 2021). When TOR is active, a high level of H3K27me3 is deposited by curly leaf (CLF), a polycomb group protein (PcG) and major H3K27 tri-methylase in plants (Mozgova and Hennig, 2015) together with like heterochromatin protein1 (LHP1), a CLF cofactor (Wang et al, 2016) in the stress response gene loci.…”
Section: Tor Signaling In Stress Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the genes with the increased DNA methylation are involved in nutrients metabolism (carbon and AAs) and phytohormones signaling transduction processes, which are tightly connected with plant growth and development (Zhu et al, 2020). Moreover, TOR could repress the transcription of stress-related genes by global maintenance of the histone modification at H3K27me3 (Dong et al, 2021). When TOR is active, a high level of H3K27me3 is deposited by curly leaf (CLF), a polycomb group protein (PcG) and major H3K27 tri-methylase in plants (Mozgova and Hennig, 2015) together with like heterochromatin protein1 (LHP1), a CLF cofactor (Wang et al, 2016) in the stress response gene loci.…”
Section: Tor Signaling In Stress Responsesmentioning
confidence: 99%
“…Recent studies also revealed that plant TORC1 is involved in stress response by epigenetic DNA modifications and histone modifications (Sharma et al, 2019; Zhu et al, 2020; Dong et al, 2021). Arabidopsis hikeshi‐like protein1 ( At HLP1) binds directly to the promoter of heat shock genes, which leads to histone acetylation and H3K4me3 accumulation to activate and maintain thermo‐memory and high‐temperature tolerance.…”
Section: Plants Tor Signaling: Downstream Targets and Biological Proc...mentioning
confidence: 99%
See 1 more Smart Citation